Comparison of 19- and 22-gauge needles in EUS-guided fine needle aspiration in patients with mediastinal masses and lymph nodes - Necla OSMANOĞLU,; Yıldıran SONGÜR,; Sema BİRCAN,; Nilgün KAPUCUOĞLU, (Turkish Journal of Gastroenterology, 2019)
-